Artificial Intelligence Research Trends in Islamic Finance: Bibliometric Analysis Using VOSviewer - Musa Zulkifli (Journal of Islamic Economics and Finance Studies, 2026)
The acceleration of digitalization has driven a paradigm shift in the financial sector towards the adoption of high technology, including Artificial Intelligence ( AI ). Although the implementation of AI such as financing automation and customer service chatbots is increasingly massive in Islamic financial institutions, literature studies that systematically map these research trends are still limited. This study aims to map the trend of scientific publications on the application of AI in Islamic finance through bibliometric analysis and literature reviews for the period 2022–2025 (with projections until 2026) to identify research roadmaps and existing research gaps. This study uses a quantitative approach with bibliometric analysis methods. Data were collected through Publish or Perish (PoP) software from the Google Scholar database with the keywords "Artificial intelligence and Islamic finance." Data visualization and mapping were performed using the VOSviewer application version 1.6.20 to analyze term relationships ( co-occurrence ) and research collaboration between authors. The findings show a significant increase in the number of publications from 2022 to a peak in 2025 with 240 articles, reflecting a shift from a conceptual exploration phase to a practical expansion phase. The cluster analysis identified four main subthemes: Digital transformation and financial inclusion, AI implementation (models, impacts, and challenges),  Technology adoption, regulatory ecosystems, and digital literacy in the digital era.